Leadership during Crisis Management - Al Remeithi, Ali Abdulrahman Abdulla (2010)
Crises cause negative impacts towards organizations, nevertheless, leaders have an important responsibility in terms of eliminating crises. The aim of the research is to realize the criticality of leadership during crisis management and reveal its necessary aspects that are required to be enhanced as well as implemented in order to prevent or deal with any crises that can cause further negative impact. In order to build the main foundation of the research, the literature review was carried out on the basis of which hypotheses based theoretical framework was developed. As the methodology, this research used quantitative, qualitative and mixed method approach. The research was based on the industries in UAE operating in the construction, investments and oil & gas sectors. The tool used to analyze qualitative data was content analysis while the tools used to analyze quantitative data were reliability test, correlation analysis and linear regression analysis. The findings of the analysis indicate areas where leaders should avoid as well as areas which leaders should implement in terms of their roles in crisis management, risks management and communication strategies.